Managing health programs and projects - Longest, Beaufort B., Jr (Jossey-Bass Public Health., 2004)
This essential resource shows how to effectively organize, implement, and evaluate health programs and projects. Managing Health Programs and Projects clearly defines and describes the work of managers in health programs and projects. The book explores the decision-making process, defines the process of communicating, probes the fundamentals of program planning, explains budgeting, covers staffing for programs and projects, and explains how leaders motivate participants in health programs and projects.